Clinical, radiological and pathological features of temporomesial tumors in the adult. A single center experience from 15 years - Meyer, Hanno S.; Wiestler, Benedikt; Hönikl, Lisa S.; Delbridge, Claire; Ketterer, Carl; Gempt, Jens; Meyer, Bernhard (Frontiers in Oncology, 2023)
The mesial temporal lobe plays a distinct role in epileptogenesis, and tumors in this part of the brain potentially have specific clinical and radiological features. Differentiating highgrade from lower-grade tumors or non-neoplastic lesions can be challenging, preventing the decision for early resection that can be critical in high-grade tumors. Methods: A prospective brain tumor database was analyzed retrospectively to identify patients with temporomesial tumors. We determined clinical features (age, sex, symptoms leading to clinical presentation) as well as neuroradiological (tumor location and the presence of contrast enhancement on initial magnetic resonance imaging (MRI)) and neuropathological findings. Results: We identified 324 temporal tumors. 39 involved the mesial temporal lobe. 77% of temporomesial tumors occured in males, and 77% presented with seizures, regardless of tumor type or grade. In patients 50 years or older, 90% were male and 80% had glioblastoma (GBM); there was no GBM in patients younger than 50 years. 50% of GBMs lacked contrast enhancement. Male sex was significantly associated with GBM. In both contrast-enhancing and non-enhancing tumors, age of 50 years or older was also significantly associated with GBM. Conclusion: In middle-aged and older patients with a mesial temporal lobe tumor, GBM is the most likely diagnosis even when there is no MRI contrast enhancement.